Pemanfaatan Media Sosial sebagai Media Pemasaran Jasa dalam Upaya Mendukung Peningkatan Perekonomian pada UMKM Pemancingan Kelapa Gading Rembang - Gideon Setyo Budiwitjaksono; Nastasya Uyun Siti Azzahra; Amanda Okky Wijaya; Evi Imtihani; Kalya Rachel Rosita; Andi Maulana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The problem that is often complained of by MSMEs in Rembang is the weak promotion strategy they carry out. According to business actors, one way for the business to grow is by introducing Indonesian local services or products to foreign countries. In this advanced era, business people must be good at using the internet. Websites, blogs, media are the biggest solutions for introducing business to the wider community. Social media is now a big opportunity for business people because social media is a source of information delivery. Instagram is already widely used around us. Everyone can use Instagram happily and easily. Instagram social media can be used as a learning tool, a means of introducing products or services and a means of buying and selling. The object of research in this paper is the Instagram social media accounts of fishing service SMEs in Rembang, Blitar, East Java. Using qualitative methods, it can be concluded that not only large companies can utilize the internet and social media as marketing media, but social media has become the main activity for business people because Instagram can facilitate communication with the public.